2022
DOI: 10.1108/jsbed-11-2021-0452
|View full text |Cite
|
Sign up to set email alerts
|

Main street business owners: aging in plain sight

Abstract: PurposeAging is the most important social-demographic issue worldwide, supported by the initiatives of the World Health Organization (WHO) in its global strategy and action plan for aging and health (Rudnicka et al., 2020). The average age of business owners in most industrialized countries is on the rise. In the United States, fifty-one percent of small private businesses are owned by someone age fifty-plus (SBA Office of Advocacy, 2018).Design/methodology/approachThe authors shed light on small business owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies have shown that the self-employed are more likely than employees to prefer late retirement (Radl, 2013;Visser et al, 2016;Zwier et al, 2021). As retirement decisions involve uncertain cost-benefit calculations, individuals are sensitive to signals from their social environment and consequently local embeddedness (Forster-Holt, 2022) or age norms (Radl, 2012) can affect them. Pending retirement can be a complex and highly emotional process in the context of entrepreneurship (Mallett and Wapshott, 2015;Morris et al, 2020).…”
Section: Entrepreneurial Exit and Exit Strategymentioning
confidence: 99%
“…Studies have shown that the self-employed are more likely than employees to prefer late retirement (Radl, 2013;Visser et al, 2016;Zwier et al, 2021). As retirement decisions involve uncertain cost-benefit calculations, individuals are sensitive to signals from their social environment and consequently local embeddedness (Forster-Holt, 2022) or age norms (Radl, 2012) can affect them. Pending retirement can be a complex and highly emotional process in the context of entrepreneurship (Mallett and Wapshott, 2015;Morris et al, 2020).…”
Section: Entrepreneurial Exit and Exit Strategymentioning
confidence: 99%